The effect of a compression bandage on the distribution of radiodense contrast medium after palmar digital nerve blocks. (23rd August 2018) - Gylling, S. M. K.; Frandsen, S. S.; Østergaard, S.; Thomsen, M. H.; Christophersen, M. T.; Krüger, T.; Jacobsen, S.
Summary: Background: Studies have shown proximal diffusion of injected drugs in perineural blocks; such diffusion may affect specificity of the nerve block. Objectives: To investigate the effect of a compression bandage applied to the pastern region on proximal diffusion of contrast medium injected over the palmar digital nerves. Study design: Experimental study, randomised cross‐over design. Methods: Radiodense contrast medium was injected over the lateral and medial palmar digital nerves of the left front limb of nine mature horses. Each horse was injected on two separate occasions, once with a 5 cm wide compression bandage applied proximal to the injection site and once without. The order of the two treatments was randomised with a wash‐out period between treatments of at least 7 days. Radiographs were obtained at 5, 10, 20 and 30 min and distribution of the contrast column assessed. Results: Proximal distribution of the contrast medium was significantly reduced (P<0.01) with compression bandage. Furthermore, the compression bandage inhibited lymphatic drainage of the injected contrast medium. Main limitations: Clinical effect of the differences in diffusion length was not assessed. Conclusions: The compression bandage reduced proximal diffusion and lymphatic drainage of contrast material causing it to stay localised around the injection site. Use of compression bandages could thus result in increased specificity of the nerve block and potentially prolong its effect.